INVESTIGATING PRAGMATICS OF APOLOGY STRATEGY: A CASE STUDY OF THE SIXTH SEMESTER ENGLISH EDUCATION STUDENTS AT INSTITUT PENDIDIKAN TAPANULI SELATAN PADANGSIDIMPUAN - Siregar, Rafika Sa'adah (Journal of Education and Teaching, 2021)
This descriptive research was carried out aimed to find out the kinds of apology strategies used by English Education Students at IPTS Padangsidimpuan and the reasons for using it. This research is a single case study, namely descriptive qualitative research which means that qualitative research has described quality. Data were taken from DCT (Discourse Completion Test) and interview. The test covers situations about violations in daily life. The research participants are sixth semester English Education Students at IPTS (Institut Pendidikan Tapanuli Selatan) who have graduated in Pragmatics course. They consist of 2 classes; A and B, and by using purposive sampling technique, as many as 10 students were selected to become participants. From the results of data analysis, as many as 10 situations given to participants, there are there are 5 known strategies used by students namely; Promise patience, indirect apology / acknowledgment of responsibility, offer of improvement, explanation or account and direct apology / expression of apology with various sub categories. and for each other's reasons. Of the strategies used by students, the strategy most often used is indirect apology / recognition of responsibility four times in situations 2, 4, 5, and 6. Keywords: Pragmatics, Speech Act, Apologies, Apology Strategies.